THE USE OF INTERACTIVE TECHNIQUES IN TEACHING THE CREATIVITY OF IBRAYIM YUSUPOV (American Journal of Pedagogical and Educational Research, 2022)
This article will talk about the use of interactive techniques in teaching the creativity of Ibrayim Yusupov.